2021
DOI: 10.1111/jcpt.13500
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and survival of women with breast cancer: A meta‐analysis of randomized controlled trials

Abstract: What is known and objective: Metformin has been suggested to confer anticancer efficacy. However, it remains uncertain whether additional use of metformin could improve survival of women with breast cancer. We performed a meta-analysis of randomized controlled trials (RCTs) to evaluate the influence of metformin on survival outcome in women with breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…Metformin has been associated with cancer, but this interplay is poorly understood in relation to HRCs (prostate, colorectal and male breast cancer) and among men of different racial backgrounds 3,12,34,35 . Our findings are in agreement with a previous study retrospective cohort study that significant associations between metformin and incident prostate and colorectal cancers 1 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Metformin has been associated with cancer, but this interplay is poorly understood in relation to HRCs (prostate, colorectal and male breast cancer) and among men of different racial backgrounds 3,12,34,35 . Our findings are in agreement with a previous study retrospective cohort study that significant associations between metformin and incident prostate and colorectal cancers 1 .…”
Section: Discussionsupporting
confidence: 92%
“…1 However, a meta-analysis of 18 cohort studies did not show an association between metformin and prostate cancer, 12 prostate cancer mortality, 2 and another study did not show improvement in survival in women with breast cancer. 34 These differences may be mainly driven by the study design. Of note, these meta-analyses 12,36 did not analyze Black or any other racial/ethnic group as a separate group.…”
Section: Metformin Use and Prostate Colorectal And Breast Cancers And...mentioning
confidence: 99%
“…Xu et al ( 64 ) reported that the pathological complete response rate of patients with diabetes and breast cancer taking metformin was 24%, which was higher than that of patients not taking metformin (8%) and also higher than that of patients without diabetes taking metformin (16%), suggesting that metformin may improve the prognosis of breast cancer in patients with diabetes. Wang et al ( 65 ) proved through randomized controlled trials that for patients with breast cancer but without diabetes, metformin could improve the prognosis of breast cancer by reducing blood insulin and testosterone levels. Tseng ( 66 ) showed that metformin significantly reduced the incidence of prostate cancer in men with type 2 diabetes mellitus.…”
Section: Metformin As An Antitumor Candidate Drugmentioning
confidence: 99%
“…However, randomized trials in phase 2 trials fail to show benefit of metformin. In non-diabetic patients, no survival effect of metformin in metastatic/recurrent breast cancer was seen when used as adjunctive therapy [ 88 , 89 , 90 ].…”
Section: Cancermentioning
confidence: 99%